A high-throughput microfluidic device for probing calcium dynamics of single cells squeezing through narrow channels. (19th September 2019) - Yuan, Wei-Mo; Shao, Jin-Yu; Xue, Chun-Dong; Liu, Bo; Qin, Kai-Rong
Abstract: To probe intracellular calcium response while single cells squeeze through narrow channels, we built a high-throughput microfluidic device where single cells can be trapped efficiently and stimulated mechanically. With this device, dozens of single cells' dynamic morphologies and intracellular [Ca 2+ ] responses under dynamic mechanical stimuli can be monitored simultaneously. We observed a two-peak [Ca 2+ ] response, which was closely coupled together with the dynamic cellular squeezing process. This type of [Ca 2+ ] response, to our knowledge, was observed for the first time. We also investigated the role of the cytoskeleton in the [Ca 2+ ] response and found that the cytoskeleton was an important regulator of [Ca 2+ ] signaling during the cellular squeezing process. In addition, we investigated the difference between the two-peak [Ca 2+ ] responses of Hela cells and HUVECs and found that one characteristic parameter could distinguish Hela cells from HUVECs.